Pengembangan Umkm Dengan Sosialisasi Digital Marketing Dan Manajemen Keuangan Terhadap Masyarakat Di Kelurahan Kedung Baruk - Tiarakasih, Dessy Anggelina; Pudjoprastiono, Herry (Jurnal Ilmiah Wahana Pendidikan, 2024)
The act of socialization can be considered a type of service to the community, especially Micro, Small and Medium Enterprises (MSMEs) and residents of Kedung Baruk Village, Rungkut District, Surabaya City, facing major challenges lack of comprehension regarding digital marketing is connected to a limited understanding of the subject and financial management. Therefore, through this outreach activity on the development of MSMEs, the aspiration is that it will enhance the knowledge, perspective, and comprehension of business individuals in Kedung Baruk Village. This, in turn, would enable them to adeptly navigate evolving times and efficiently manage their businesses by harnessing available opportunities. Entrepreneurs and inhabitants of Kedung Baruk Village were provided with insights into the significance of online marketing, referred to as digital marketing. Additionally, they were educated on the procedures involved in crafting a logo for identity and marketing purposes, along with guidance on business financial management. The execution of this service initiative involves a lecture method by UPN Veteran East Java students and a lecturer, Subsequent to a question and answer session. The outcomes of this information dissemination included very positive responses from the participants, as seen from their active participation in listening and asking questions. Apart from that, this MSME development outreach program is considered useful and has the potential to implemented well through the participants in managing their businesses.